Explosive mutation accumulation triggered by heterozygous human Pol ε proofreading-deficiency is driven by suppression of mismatch repair - Hodel, Karl P; de Borja, Richard; Henninger, Erin E; Campbell, Brittany B; Ungerleider, Nathan; Light, Nicholas; Wu, Tong; LeCompte, Kimberly G; Goksenin, A Yasemin; Bunnell, Bruce A; Tabori, Uri; Shlien, Adam; et al. (eLife, 2018)
Tumors defective for DNA polymerase (Pol) ε proofreading have the highest tumor mutation burden identified. A major unanswered question is whether loss of Pol ε proofreading by itself is sufficient to drive this mutagenesis, or whether additional factors are necessary. To address this, we used a combination of next generation sequencing and in vitro biochemistry on human cell lines engineered to have defects in Pol ε proofreading and mismatch repair. Absent mismatch repair, monoallelic Pol ε proofreading deficiency caused a rapid increase in a unique mutation signature, similar to that observed in tumors from patients with biallelic mismatch repair deficiency and heterozygous Pol ε mutations. Restoring mismatch repair was sufficient to suppress the explosive mutation accumulation. These results strongly suggest that concomitant suppression of mismatch repair, a hallmark of colorectal and other aggressive cancers, is a critical force for driving the explosive mutagenesis seen in tumors expressing exonuclease-deficient Pol ε.
Keywords: Genome Stability; Mutagenesis; DNA Replication; DNA Polymerase